Perancangan dan Pengembangan Vıdeo Company Profıle Sebagaı Medıa Promosı Hello Educatıon - heru Wijayanto Aripradono; Wandi Wandi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
The design of the company profile is made as a promotional media, introduces and conveys information to potential customers. In the video company profile, which contains a company profile, Hello Education’s private tutoring programs and learning systems. The collection technique uses the step method by using the data obtained in the form of video. Data collection was carried out using observations and interviews, making video company profile design using the Adobe Premier Pro CC 2017 application as the design progress. The results of the company profile video have been implemented on YouTube and Instagram, with that it has been proven that customers can increase by using the implemented video company profile